Tsinghua Universities and Christianity - Bieler, Stacey (Journal of Research for Christianity in China (JRCC), 2025)
Education is important to build a powerful country. Chinese Christians and American Christians play important roles in Chinese university. Most of them come from America or had studied aboard. They become college professor to teach Chinese students western high tech still and colorful culture. Also, the Christian teachers host some Christian activity in order to build character development, service, social action, and leadership. They founded Tinghua Univerisity in Beijing and Tinghua university in Taiwan. Mei yiqi is one of them, had served as president of Tsinghua in Beijing from 1931-48, became the first president in the founding of National TsingHua University in Hsinchu in Taiwan in 1956.